CAVERNOUS HEMANGIOMALIKE CHANGES IN A CHOROIDAL MELANOMA AFTER BRACHYTHERAPY. Issue Volume 10:Issues 1(2016:Winter) (2016) - Lopez, Michael; Johnson, Jean G.; Margo, Curtis E.; Pavan, Peter R.
Abstract : Purpose: To describe a degenerative vascular change in a treated choroidal melanoma that clinically simulated late treatment failure. Methods: Observational case report. Results: A 79-year-old man with choroidal melanoma treated 15 years earlier with iodine-125 brachytherapy demonstrated substantial increase in size of this once stable tumor. The eye was removed because of concern of late treatment failure. Histologically, the tumor consisted of melanocytes with no mitotic activity and virtually no Ki-67 expression. Roughly half the lesion was composed of cavernous blood-filled spaces lined by bland CD34 + and CD31 + endothelial cells. Conclusion: Late degenerative changes in the vasculature of treated uveal melanoma can result in tumor enlargement, which may raise clinical concerns over treatment failure and neoplastic potential. Abstract : A choroidal melanoma treated 15 years earlier with iodine-125 brachytherapy demonstrated increase in size. Histologically, roughly half the lesion was composed of cavernous blood-filled spaces. Late degenerative changes in the vasculature of treated uveal melanoma can result in tumor enlargement and concerns over treatment failure.